Implementasi Strategi Pemasaran Melalui Kegiatan Rebranding Produk UMKM Jenang Legend Lek Siti di Kota Blitar - Nanda Nur Humairoh Arifin; Jojok Dwiridotjahjono (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
People who produce typical food products certainly have a business that generates profits in the sale of the products they make. By increasing sales, it is necessary for a brand in a product to provide benefits for both producers and consumers. In product development, KKN students carry out a rebranding activity for UMKM’s. Rebranding is an effort made to completely change or renew an existing brand so that it becomes better by not ignoring the company's original purpose, which is profit-oriented. In order to find out the obstacles faced by UMKM’s in the Blitar sub-district, it is necessary to conduct a qualitative research method with the types of data collection observation, interviews and documentation. And the results of this rebranding chose one of the UMKM’s in Blitar Village by assisting in logo rebranding activities, packaging to making taglines.